Growth and survival performance of Mrigal Cirrhinus mrigala fingerlings in high temperature at laboratory condition (Research in Agriculture Livestock and Fisheries, 2020)
Global warming is expected to affect the aquatic ecosystem and aquaculture industry. In the current experiment, we have observed growth and water quality of Indian major carp mrigal (Cirrhinus mrigala) exposed to three different temperature regimes, such as 30, 33 and 36°C representing T1, T2 and T3, respectively for 60 days. One hundred and twenty fish were used, kept in 6 Aquarium, and were exposed to the different temperature. Highest body weight gain and lowest feed conversion ratio (FCR) was recorded at T2. The highest specific growth rate was recorded at T2 followed by T1 and T3. The optimum temperature range for growth was 30 to 33°C. Survival at different acclimation temperatures was between 90.00±0.00, 90.0±0.00 and 75.00±0.00%, from lower to higher acclimation temperatures. Dissolved oxygen decreased and free CO2 increased significantly (P